Parental caregiving of children with cancer and family impact, economic burden: nursing perspectives. (March 2014) - Williams, Phoebe D.; Williams, Kirstin A.; Williams, Arthur R.
<x xml:space="preserve">Abstract</x> Pediatric cancer diagnoses affect the entire family: parents, well siblings, the ill child, and others. The objective of this study was to review nursing studies on parental caregiving of children with cancer, family impact, and costs. The study used inclusion/exclusion criteria and family systems theory, self/dependent-care, and symptom management (monitoring, alleviation) concepts. Regarding "levels of evidence, " 3 studies were Level II; 7 were Level IV; 7 were Level VI; 1 review was Level V and the second was Level I. Of 19 studies: 11 were qualitative; 4, quantitative; 2 were mixed methods. Content analysis themes were: Parental caregiving and family impact, economic burden. Conclusions were that (a) qualitative studies are predominant; findings supported quantitative findings; (b) quantitative nursing studies are less common: found one longitudinal, randomized controlled trial (RCT) focused on outcomes of an intervention for well siblings and parents, implemented by Clinical Nurse Specialists, CNSs; (c) few quantitative studies with large samples were found, especially ones with theoretical models of the family system and measures of illness impact on families; and (d) "mixed methods" longitudinal nursing research is illustrated. There is a need for "evidence-based" practice (EBP) nursing studies of interventions focused on parent education/support/assistance; respite care, and increasing family/well sibling knowledge/other information on the child's illness.